A SUITABLE EDUCATION FOR EVERY CHILD: THE IMPORTANCE OF AN INCLUSIVE APPROACH - Makhmudova Muborak (Bright Mind Publishing, 2025)
This article analyzes the essence of inclusive education, its importance and practical methods of application. Inclusive education is considered as a system that allows children with different needs to receive education on equal terms. The article discusses the role of educators, the tasks of educational institutions in creating an inclusive environment, and the participation of society in this process. The results of the study show that through an inclusive approach, it is possible to increase the effectiveness of education and strengthen social tolerance not only for children with special needs, but also for all students.
Keywords: Inclusive education, equal opportunities, special needs, pedagogy, integration, educational methods, quality of education, tolerance.